2020
DOI: 10.4236/jbbs.2020.1010024
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Influencing Factors of Comprehensive Rehabilitation Therapy in Patients with Aneurysmal Subarachnoid Hemorrhage

Abstract: This study aimed to determine the effectiveness of comprehensive rehabilitation for patients with aneurysmal subarachnoid hemorrhage (aSAH) and to explore the factors influencing the prognosis of rehabilitation. This was a retrospective study. Twenty-five patients with aSAH were treated with physical therapy, occupational therapy, speech therapy, cognitive therapy, music therapy, Chinese acupuncture, hyperbaric oxygen, and transcranial magnetic stimulation. The general data of all patients were collected, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Research has shown potential protective effects of HBOT in both preclinical studies and in various SAH cases as well. [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown potential protective effects of HBOT in both preclinical studies and in various SAH cases as well. [20][21][22].…”
Section: Introductionmentioning
confidence: 99%